C–H alkenylation/cyclization and sulfamidation of 2-phenylisatogens using N-oxide as a directing group. Issue 71 (20th August 2019) - Guo, Lingmei; Tang, Baolan; Nie, Ruifang; Liu, Yanzhao; Lv, Shan; Wang, Huijing; Guo, Li; Hai, Li; Wu, Yong
Abstract : Ru(ii )-Catalyzed C–H alkenylation/cyclization and Ir(iii )-catalyzed C–H sulfamidation provided indol-3-one derivatives and sulfamidated 2-phenylisatogens respectively, with good yields and excellent functional group tolerance. Abstract : The first example of transition-metal-catalyzed C–H activations of 2-phenylisatogens with alkynes and sulfonyl azides has been developed using N -oxide as the directing group. Ru(ii )-Catalyzed C–H alkenylation/cyclization and Ir(iii )-catalyzed direct C–H sulfamidation proceeded with good yields and excellent functional group tolerance. Importantly, these two transformations provided straightforward routes for the synthesis of indol-3-one derivatives and sulfamidated 2-phenylisatogens respectively, which might be of considerable bioactivities.